On the Modelling of Laser Thermal Fracturing of Hard Rock - Yevtushenko, A.A.; Matysiak, S.J.; Ivanyk, E.G. (Engineering Transactions, 1997)
The Paper deals with the nonstationary problem of elastic half-space heated by laser beam. On the basis of the uncoupled linear thermoelasticity, the distribution of temperature and stresses in the body is obtained. By using the theory of brittle fracture given by Griffith and McClintock and Walsh, the fracture trajectories are presented for three kinds of rocks: granites quartzites and gabbros for a given radius of the heating region and its intensity.